Near-Field Body-Wave Extraction From Ambient Seafloor Noise in the Nankai Subduction Zone - Tonegawa, Takashi; Kimura, Toshinori; Araki, Eiichiro (Frontiers in Earth Science, 2021)
Ambient noise correlation is capable of retrieving waves propagating between two receivers. Although waves retrieved using this technique are primarily surface waves, the retrieval of body waves, including direct, refracted, and reflected waves, has also been reported from land-based observations. The difficulty of body wave extraction may be caused by large amplitudes and little attenuation of surface waves excited by microseisms, indicating that body wave extraction using seafloor records is very challenging because microseisms are generated in ocean areas and large amplitudes of surface waves are presumably observed at the seafloor. In this study, we used a unique dataset acquired by dense arrays deployed in the Nankai subduction zone, including a permanent cabled-network of 49 stations, a borehole sensor, and 150 temporary stations, to attempt to extract near-field body waves from ambient seafloor noise observed by multivariate sensors of broadband and short-period seismometers, differential pressure gauges (DPGs), and hydrophones. Our results show that P waves are extracted only in the DPG-record correlations at a frequency of 0.2-0.5 Hz, which can be seen up to a separation distance of two stations of 17 km with an apparent velocity of 3.2 km/s. At 1–3 Hz, P waves are observed only in the vertical-record correlations up to a separation distance of 11 km with an apparent velocity of 2.0 km/s. These velocity differences reflect the vertical velocity gradient of the accretionary prism, because the P waves at low frequencies propagate at relatively long distances and therefore the turning depth is greater. Moreover, the long-period and short-period P waves are observed at the slope and flat regions on the accretionary prism, respectively. To investigate the retrieved wavefield characteristics, we conducted a two-dimensional numerical simulation for wave propagations, where we located single sources at the sea surface above the flat and slope bathymetry regions. Based on our observations and simulations, we suggest that the retrieval of near-field body waves from ambient seafloor noises depends on the relative amplitudes of P and other surface waves in the ambient noise wavefield, and those are controlled by the subseafloor velocity structure, seafloor topography, and water depth.